Development of a hybrid energy harvesting system based on thermoelectric and electromagnetic generators for use in industrial electric motors - de Oliveira, Luiz Fernando Pinto; de Oliveira Morais, Flávio José [UNESP]; Manera, Leandro Tiago (My University, 2024)
In Industry 4.0, advanced systems for predicting maintenance of industrial electric motors are being developed. These systems use electronic sensors and wireless communication in low-power circuits. To enable self-sustaining devices and long-term monitoring strategies, energy harvesting techniques are employed. This paper describes a hybrid energy harvesting system based on a Thermoelectric Generator (TEG) and Current Transformer (CT) that is used in an Internet of Things (IoT) vibration monitoring system for industrial electric motors. The proposed electronic circuit is designed to operate in extreme conditions of electrical energy shortage and allows for energy supply via capacitor, supercapacitor, and backup battery. A new mechanical coupling system is also presented for attaching TEGs to motors. The integration of TEGs and CTs resulted in a maximum power output of 320 μW and energy autonomy of 80.76 min (via TEG), which was further improved to 1540 μW after 10.32 min (via CT). The energy autonomy of the IoT device was extended from 2 to 33 days by using a hybrid energy storage circuit, exceeding the energy requirements for making the IoT device self-sustaining by 54.21%.
Keywords: CT; Current transformer; Energy harvesting; Internet of Things; TEG; Thermoelectric generator; Ultra low-power